Patch-to-Seq and Transcriptomic Analyses Yield Molecular Markers of Functionally Distinct Brainstem Serotonin Neurons - Mouradian, Gary C.; Liu, Pengyuan; Nakagawa, Pablo; Duffy, Erin; Gomez Vargas, Javier; Balapattabi, Kirthikaa; Grobe, Justin L.; Sigmund, Curt D.; Hodges, Matthew R. (Frontiers in Synaptic Neuroscience, 2022)
Acute regulation of CO2 and pH homeostasis requires sensory feedback from peripheral (carotid body) and central (central) CO2/pH sensitive cells – so called respiratory chemoreceptors. Subsets of brainstem serotonin (5-HT) neurons in the medullary raphe are CO2 sensitive or insensitive based on differences in embryonic origin, suggesting these functionally distinct subpopulations may have unique transcriptional profiles. Here we used Patch-to-Seq to determine if the CO2 responses in brainstem 5-HT neurons could be correlated to unique transcriptional profiles and/or unique molecular markers. Firing rate changes with hypercapnic acidosis were measured in fluorescently labeled 5-HT neurons in acute brainstem slices from transgenic, Dahl SS (SSMcwi) rats expressing T2/ePet-eGFP transgene in Pet-1 expressing (serotonin) neurons (SSePet1-eGFP rats). Then, single cell RNA sequencing (scRNAseq) and bioinformatic analyses were performed on the intracellular contents. Low baseline firing rates were a distinguishing feature of CO2 sensitive 5-HT neurons. scRNAseq of these recorded neurons revealed 166 differentially expressed genes among CO2 sensitive and insensitive 5-HT neurons. Pathway analyses yielded novel predicted upstream regulators, including the transcription factor Egr2 and Leptin. Additional bioinformatic analyses identified 6 candidate gene markers of CO2 sensitive 5-HT neurons, and 2 selected candidate genes (CD46 and Iba57) were both expressed in 5-HT neurons determined via RNAScope. Together, these data provide novel insights into the transcriptional control of cellular chemoreception and provide unbiased candidate gene markers of CO2 sensitive 5-HT neurons. Methodologically, these data highlight the utility of the patch-seq technique in enabling the linkage of gene expression to specific functions, like CO2 chemoreception, in a single cell to identify potential mechanisms underlying functional differences in otherwise similar cell types.